Peningkatan kapasitas guru SD di Kecamatan Bambanglipuro dalam akomodasi siswa berkebutuhan khusus - Purwandari, Ernisa; Suparno, Suparno; Praptiningrum, Nurdayati; Hermanto, Hermanto; Rudiyati, Sari; Syamsi, Ibnu; Haryanto, Haryanto (Piramida Akademi, 2023)
This study aims to increase teachers' knowledge about (1) assessment of students with special needs; (2) choosing the right learning strategy for students with special needs; (3) compiling learning programs for students with special needs in schools providing inclusive education. This research is action research. The research subjects were 44 elementary school teachers in Cluster 01 UPT PP, Bambanglipuro District. Collection techniques are used with tests, observations, interviews, and documentation. Data analysis was performed by descriptive analysis. The results showed an increase in three areas, namely: (1) teachers' knowledge in conducting assessments of children with special needs according to the characteristics of their needs, (2) teachers' knowledge in choosing learning strategies for children with special needs; (3) knowledge and compiling learning programs for children with special needs.